L’architecte Pierre Le Mousseux (1687 - 1740) : ses dernières années en Bourgogne - Brigitte Fromaget (In Situ)
Seen primarily as an “execution” architect, Pierre Le Mousseux has never been studied as an individual creator. His life and his work are documented primarily during the periods when he collaborated with the King’s architects: from 1716 to 1724 when he was in Normandy and built the royal stud farm of Le Pin, under the direction of Robert de Cotte; and from 1725 to 1730 when he was at Rennes, under the direction of Jacques Gabriel for the reconstruction of the city. In 1733 he came to Dijon where the King’s architect again called on his assistance for the construction of a staircase and new wing of the States Palace